2014
DOI: 10.1038/aps.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid attenuates insulin resistance and improves glucose metabolism in high fat diet-fed mice

Abstract: Aim: To investigate whether alpha-lipoic acid (ALA) could attenuate the insulin resistance and metabolic disorders in high fat diet-fed mice. Methods: Male mice were fed a high fat diet (HFD) plus ALA (100 and 200 mg·kg -1 ·d -1 ) or HFD plus a positive control drug metformin (300 mg·kg ) for 24 weeks. During the treatments, the relevant physiological and metabolic parameters of the mice were measured. After the mice were euthanized, blood samples and livers were collected. The expression of proteins and genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Increased gluconeogenesis occurs during substantial hepatic insulin deficiency, thus likely representing the course of type 2 diabetes mellitus (40). Previous results showed that G6Pase and PEPCK, the key gluconeogenic enzymes, were significantly increased in the liver of HFD mice, consistent with our current findings (41,42). As a potential cause of CTregulated hepatic glucose metabolism, the expression levels of G6Pase and PEPCK were significantly decreased upon CT treatment ( Figure 8).…”
Section: Discussionsupporting
confidence: 89%
“…Increased gluconeogenesis occurs during substantial hepatic insulin deficiency, thus likely representing the course of type 2 diabetes mellitus (40). Previous results showed that G6Pase and PEPCK, the key gluconeogenic enzymes, were significantly increased in the liver of HFD mice, consistent with our current findings (41,42). As a potential cause of CTregulated hepatic glucose metabolism, the expression levels of G6Pase and PEPCK were significantly decreased upon CT treatment ( Figure 8).…”
Section: Discussionsupporting
confidence: 89%
“…The current findings suggest that α-lipoic acid is beneficial and thus should be considered for routine administration in patients with diabetes and peripheral neuropathy [24]. A study by Yang et al [25] demonstrated that metformin might be effective for reducing blood glucose and promoting glucose uptake and utilization and that ALA might be effective for improving insulin sensitivity and activating insulin-signaling pathways. They demonstrated that ALA enhances hepatic insulin sensitivity and prevents the development of Non-alcoholic fatty liver disease, furthermore, ALA ameliorates glucose metabolism by modulating the insulin-signaling pathway.…”
Section: Discussionmentioning
confidence: 68%
“…ALA also attenuated high-fat diet-induced hyperglycemia and insulin resistance significantly in mice (40). Dietary supplementation of ALA in aged rats was also reported to improve mitochondrial function and reduced oxidative insults in rat models (12).…”
mentioning
confidence: 86%